Quranic Epistemology in Islamic Curriculum Development: A School-Based Management Perspective - Nur Afif (SUJANA: Education and Learning Review, 2026)
Islamic educational institutions operating within decentralized governance systems face a persistent tension between national curriculum requirements and the normative demands of Quranic educational philosophy. While School-Based Management (SBM) grants schools meaningful autonomy over curriculum planning and institutional decision-making, existing scholarship has not adequately theorized how Quranic epistemological principles might actively govern the structural logic of curriculum development rather than simply inform its content. This study addresses that gap through a library-based qualitative inquiry that brings Quranic educational philosophy into systematic dialogue with contemporary curriculum theory and SBM governance literature. The analysis identifies three Quranic principles, namely tauhid, iqra, and amanah, as foundational curriculum architects that generate operationalizable demands on educational objectives, content selection, pedagogical methodology, and learning evaluation simultaneously. The findings further demonstrate that SBM provides an institutional governance structure compatible with Quranic-based curriculum development when three conditions converge: values-driven principal leadership, structured teacher participation in curriculum design, and community engagement anchored in a shared Islamic educational vision. These findings extend Bandur et al.'s governance argument by adding an epistemological dimension, extend Khanal and Guha's climate findings by foregrounding the normative content of autonomous decisions, and partially contest Alkandari's competency-based framing by insisting that epistemological foundations must precede implementation questions. The study contributes a theoretically grounded framework that school leaders, curriculum designers, and policymakers in Indonesia's Islamic educational system can use to align institutional practice with Quranic values within decentralized governance structures.